PENENTUAN KEY PERFORMANCE INDICATORS DENGAN METODE PERFORMANCE PRISM (STUDI KASUS PROGRAM STUDI TEKNIK INDUSTRI SEKOLAH TINGGI TEKNOLOGI DUMAI) - Mesra, Trisna; Fitra, Fitra; Abdillah, Nuryasin; Faisal, Rudi; Melliana, Melliana; Nurlaila, Qomaratun (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
Dumai College of Technology, as the only Technical Higher Education Institution in Dumai City, continues to be determined to always improve its performance. The Industrial Engineering study program seeks to make improvements to improve the quality of education, besides that it is also necessary to measure performance as an effort to improve performance in every aspect of the study program's performance. This research is related to the performance assessment of the Industrial Engineering study program at the Dumai College of Technology using the Performance Prism method. This method has five aspects, namely top and bottom are stakeholder satisfaction which is obtained from distributing questionnaires and stakeholder contribution which is obtained by interviews which are used to identify study program objectives which are then used to identify strategies, processes and capabilities. Key Performance Indicators (KPI) for the Industrial Engineering Study Program which has been formed from the processes and capabilities that have been identified are 19 KPIs